Determination of stature from female sternum in central Delhi population - Gupta, Mohit; Kumar Mittal , Anil (Journal of Indian Academy of Forensic Medicine, 2019)
Identification is one of the important aspects dealt with in forensic anthropology. It is necessary in cases of mass disasters or otherwise  when no clue is present regarding the identity of individual. Bones have been used previously for identification by determining race,  age, sex and stature. However, limited studies for estimation of stature from Sternal bone are available in literature. This study was  conducted on a population of Delhi, India, to assess the usefulness of Sternal bone for determining stature. Results indicated that length  of the Manubrium (R=0.631, SEE=5.67) is a useful parameter for stature estimation from female sternum while length of  Mesosternum (R=0.0.098, SEE=7.28) and Sternal length (R=0.192, SEE=7.181) are not effective parameters. Regression equations  were developed for each parameter. We also find that regression equations developed by researchers for other population samples are  not useful for our population sample.
Keywords: Stature; Sternum; Female; Identification